Testing Criterion Correlations With Scale Component Measurement Errors Using Latent Variable Modeling. Issue 3 (4th May 2017) - Raykov, Tenko; Marcoulides, George A.; Gabler, Siegfried; Lee, Youngjun
Abstract : A latent variable modeling method for testing criterion correlations with measurement error terms in multicomponent measuring instruments is outlined. The approach is based on an application of the Benjamini–Hochberg multiple testing procedure and can be used when assumptions of validity estimation related procedures need to be examined. The method also allows studying the extent to which criterion validity coefficients might be due to the relationship between a presumed underlying latent construct evaluated by a psychometric scale and a criterion variable, or could be a consequence of the relation between measurement error in the overall scale score and the criterion. The discussed procedure is widely applicable with popular latent variable modeling software, and is illustrated using a numerical example.